Cultural heritage: capturing Sarawak's visual heritage / Valerie Michael - Michael, Valerie (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The population of Sarawak consists of numerous indigenous groups, food, customs, traditions, and languages. This led to the contribution of cultural identity in the framework of cultural heritage in Sarawak. As time flies, maintaining and preserving the culture becomes part of educating the young generation and the public. One of the platforms to promote cultural heritage is through visual art and through highlighting the subject matter of the art.